Utilization of Tofu Liquid Waste as Organic Fertilizer on the Growth and Production of Paddy Rice Plants (Oryza sativa L) - Wili Heriko; Tri Nopsagiarti; Angga Pramana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
This research has been carried out in Kedundung Island Village, Central Kuantan District, Kuantan Singingi Regency. This research takes place for approximately four months starting from November 2017 until March 2018. This study aims to determine the effect of Tofu Liquid Waste as Liquid Organic Fertilizer on Plants and Production of Paddy Rice (Oriza sativa L). The parameters observed in this study include: plant height, age of flowering, age of harvest, number of productive tillers, and dry grain weight. This study aims to determine the effect of Tofu Liquid Waste as Organic Fertilizer on the Growth and Production of Rice Field Crops. The design used in this study is a Non Factorial Randomized Block Design (RBD) consisting of one factor, namely factor A (Tofu Liquid Waste) consisting of 4 levels: A0 (control), A1 (600 mL/plot), A2 (1200 mL/plot), A3 (1800 mL/plot). The observational data from each treatment were statistically analyzed and continued with the Next Test of Honestly Significant Difference at the 5% level. The results showed that the Tofu Liquid Waste treatment had a significant influence on the parameters of observation of Plant Height, Flowering Age, Harvest Age, Number of Productive Tillers and Dry Grain Weight. The best treatments were A3 for observation of Plant Height (124.91 cm), Flowering Age (73.99 days), Harvest Age (95.74 days), Number of Productive Tillers (50.91 stems), and Dry Grain Weight (100.16 g)